EFFECT OF LEPTIN ON IN-VITRO MATURATION OF OOCYTES AND ON EARLY EMBRYONIC DEVELOPMENT IN BUFFALOES - SINGH, BEERENDRA; PRASAD, SHIV; GUPTA, H P (The Indian Journal of Animal Reproduction, 2023)
The present study was aimed to assess the physiological function of Leptin on in-vitro maturation of oocytesand early embryonic development to increase the efficiency of in-vitroembryo production in buffaloes. The oocyteswere maturated in 199 medium supplemented with 10% FBS, 0.51,.1g/ml FSH, 101U/ml LH, 11,.19/ml estradiol-17p,20ng/ml EGF and 50 μM cysteamine in four groups i.e. Group-I (without leptin), Group-I I (1 Ong/ml leptin), GroupIll(20ng/ml leptin) and Group-IV (30ng/ml leptin) in CO2 incubator at 37°C temperature, 5% CO2 and high humidity.The matured oocytes were fertilized in-vitro in modified synthetic oviductal fluid (mSOF) containing 1 Ong/ml heparin.Presumptive zygotes were cultured in mSOF for 7 days to study embryonic development. The oocytes maturationrates were 76.55, 83.25, 90.14 and 92.16 %, respectively in groups I, II, Ill and IV, cleavage rates were 48.75,59.77, 70.83 and 71.50%, embryonic development to morula stage were 41.03, 50.96, 58.82 and 57.34%% andblastocyst development rates were 25.64, 30.77, 44.12 and 44.06 %. The oocytes maturation, cleavage, morulaand blastocyst development rates were significantly higher in leptin supplemented groups. From the presentstudy, it may be concluded that leptin at the concentration of 20ng/ml in maturation medium significantly (P
Keywords: Buffalo; Leptin; Oocytes; in-vitro maturation; in-vitro fertilization; in-vitro culture